2018
DOI: 10.32931/io1802r
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Design and Synthesis of Polymers from Silicon- Containing Norbornenes for Membrane Gas Separation

Abstract: The present review highlights recent approaches to the synthesis of highly permeable polymers by metathesis and addition polymerization of silicon-containing norbornenes. The main focus is on the authors' own works that utilize Me 3 Sisubstituted exo-tricyclononenes as highly reactive norbornenetype monomers for polymerization. The basic relationships between polymer structures and their gas permeability characteristics are considered. The possibility of tuning the gas transport properties of polymers (permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 106 publications
(198 reference statements)
0
2
0
Order By: Relevance
“…16,17 To overcome this disadvantage, the [2s + 2s + 2p]-cycloaddition of vinylsilanes with quadricyclane was realized (Scheme 1b). 18 This selectively gives the exo-isomer, but only "activated" vinylsilanes (which contain chlorine atoms at silicon) were active in this reaction. [19][20][21][22] This limits the scope of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 To overcome this disadvantage, the [2s + 2s + 2p]-cycloaddition of vinylsilanes with quadricyclane was realized (Scheme 1b). 18 This selectively gives the exo-isomer, but only "activated" vinylsilanes (which contain chlorine atoms at silicon) were active in this reaction. [19][20][21][22] This limits the scope of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Russia). Poly(3-(tributoxysilyl)tricyclononene-7) (PTBSN, structure V, Figure 2 ) was prepared according to methodology described in [ 15 ] (Scheme 4), [ 16 ] via ring opening metathesis polymerization using WCl 6 in toluene catalyst in Institute of Petrochemical Synthesis, RAS, and was used as is. The primary investigation of properties showed that in GC separation conditions PTBSN had to be in visco-elastic state, as the glass transition temperature of this polymer was −32 °C (241 K).…”
Section: Methodsmentioning
confidence: 99%